Florística e fitossociologia de um trecho de floresta ombrófila densa das terras baixas na Reserva Biológica de Sooretama, Linhares - ES - Paula, Alessandro de (2006)
The aim of this work was to analyze the floristic composition and horizontal structure of a stretch of the arboreal vegetation in the Biological Reserve of Sooretama. The survey was restricted to a phytosociological sample done on one hundred contiguous portions of 10 x 10 meters. Individuals with PBH ≥ 15 cm were sampled. The forest was segmented in three vertical strata, allowing EIV calculation. A meter and a meter width were used as first center class. A total of 1519 individuals were sampled, distributed in 265 species, 138 genera and 44 families. The Shannon s Index (H ) found was 4,87 nats. In relation to the threatened species, 16 consist in the Red List of Espírito Santo State. The Biological Reserve of Sooretama obtained 57% of similarity with the Natural Reserve of CVRD. The species Rinorea bahiensis (Moric.) Kuntze prevailed in the three strata, with has the largest EIV. The group of the late secondary stood out in all the strata. The stand was considered at advanced successional stage.